2014
DOI: 10.1590/s0080-6234201400005000003
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric patient classification system: improvement of an instrument

Abstract: RESUmo Este estudo teve como objetivos avaliar a reprodutibilidade interavaliadores do ins-trumento para a classificação de pacientes pediátricos portadores de câncer; verificar se o instrumento de classificação de pa-cientes é adequado a pacientes pediátri-cos portadores de câncer e elaborar uma proposta de modificação do instrumento, permitindo a adaptação para pacientes pediátricos oncológicos. Foram avaliados, na unidade de internação pediátrica de um Hospital de câncer, 34 pacientes pe-las equipes de médi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
48
0
34

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(83 citation statements)
references
References 13 publications
1
48
0
34
Order By: Relevance
“…To reach the proposed objectives, four measurement instruments were applied: APROCENF scale ( 15 ) ; Two Patient Classification Instruments (PCIs) (one for adult ( 13 ) and another pediatric ( 17 ) ) and the Nursing Activities Score (NAS) ( 18 ) . It is noteworthy that the first three instruments ( 13 , 15 , 17 ) were constructed and had their psychometric properties tested in Brazil, respectively in 2017, 2013 and 2014, and the last ( 18 ) , was validated for Brazilian culture in 2009.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…To reach the proposed objectives, four measurement instruments were applied: APROCENF scale ( 15 ) ; Two Patient Classification Instruments (PCIs) (one for adult ( 13 ) and another pediatric ( 17 ) ) and the Nursing Activities Score (NAS) ( 18 ) . It is noteworthy that the first three instruments ( 13 , 15 , 17 ) were constructed and had their psychometric properties tested in Brazil, respectively in 2017, 2013 and 2014, and the last ( 18 ) , was validated for Brazilian culture in 2009.…”
Section: Methodsmentioning
confidence: 99%
“…It is noteworthy that the first three instruments ( 13 , 15 , 17 ) were constructed and had their psychometric properties tested in Brazil, respectively in 2017, 2013 and 2014, and the last ( 18 ) , was validated for Brazilian culture in 2009.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to the lack of consensus in the literature about the number of people needed to compose the expert panel, we chose to use the sample of nine people, the highest number among the studies found (16)(17)(18)(19) .…”
Section: Validation Of Standard Operating Proceduresmentioning
confidence: 99%